Fatty acid regulation of feeding in Caenorhabditis elegans reveals the potential ancestral origin of a GLP-1-like multiagonist signaling system - Feimei Zhu; Jorge Iván Castillo-Quan; Takafumi Ogawa; Ziyun Wu; Lang Ding; Mansi Sura; Yoshiyuki Watanabe; Hannah Lentschat; L. Paulette Fernández-Cárdenas; Ugur Dag; Annette Beck-Sickinger; Meng C. Wang; et al. (Proceedings of the National Academy of Sciences, 2026)
Regulation of food intake in mammals is complex and controlled by an interplay between hedonic and homeostatic signals, including hormones like leptin, which senses fat storage and suppresses food intake. Caenorhabditis elegans lack leptin and leptin receptors but still exhibit controlled eating. Here, we show that in C. elegans eating can be regulated by a balance between saturated and monounsaturated fatty acids interacting with transcriptional pathways regulating lipid synthesis, c-AMP response element binding protein and AMP kinase. This effect is mediated at the endoplasmic reticulum through formation of phospholipids and activation of the IRE-1 sensor in the nervous system, which controls behavior through neuronal serotonin and the G-protein-coupled ligand/receptor pair PDF-1/PDFR-1. We show that this peptide/receptor pair may be an ancestral precursor of the whole family of GLP-1/GIP-related peptides and their receptors. Indeed, administration of a 37 amino acid peptide derived from PDF-1 resulted in a reduction in body weight and improved insulin sensitivity in mice. In worms, signaling through this pathway induced food-leaving behavior on concentrated food and roaming behavior on dispersed food, a state we have termed “food-apathy,” paralleling pharmacologic effects of GLP-1/GIP-related peptides in humans. These findings highlight the potential evolutionary origin of this family of hormones and their receptors, and its link to metabolic and neuronal responses in control of feeding behavior.